Performance analysis of Horner's rule-based canonical signed digit lifting architecture for two-dimensional discrete wavelet transform. (2017) - Geetha, V.; Murugesan, G.
The high performance of image compression is needed greater as digital image finds its way into many areas of everyday life. JPEG 2000 is one of the best image compression standards in which DWT (Discrete Wavelet Transform) is used. In this paper, an efficient two-dimensional (2D) DWT 9/7 and 6/10 filter based on Horner's Rule with Canonical Signed Digit is proposed. Canonical Signed Digit is based on the positional values of 1's in the representation, whereas Horner's rule-based Canonical Signed Digit is based on the distance between the positions of 1's. Implementing the Canonical Signed Digit and Horner's Rule with Canonical Signed Digit architectures of 9/7 and 6/10 filters in Synopsys IC Compiler with 90 nm technology shows the reduction of 31.07% and 36.86% in the total dynamic power along with reduction of 25.72% and 31.17% in the total area, respectively, when compared with the existing method.